2015
DOI: 10.1016/j.envint.2015.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide levels and environmental risk in aquatic environments in China — A review

Abstract: China is one of the largest producers and consumers of pesticides in the world today. Along with the widespread use of pesticides and industrialization, there is a growing concern for water quality. The present review aims to provide an overview of studies on pesticides in aquatic environments in China. The levels in the water, sediment and biota were scored according to a detailed environmental classification system based on ecotoxicological effect, which is therefore a useful tool for assessing the risk thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
83
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(103 citation statements)
references
References 35 publications
2
83
0
1
Order By: Relevance
“…Though the use of these legacy compounds was banned in the early 1980s, HCHs and DDTs were detected at all sediment depths in SGZ and accounted for a large proportion of the OCPs present in the core (30.5 ± 7.5% and 60.9 ± 8.1% of ΣOCP, respectively). The high detection frequency of HCHs and DDTs in the SGZ core is supported by other studies in South China (Guo et al, 2009;Grung et al, 2015). It was assumed that the same trends would be observed for the RLY core as well, however surprisingly, that was not the case, as HCHs and DDTs were rarely detected in the core, and rather chlordanes were detected at higher concentrations (11.2-98.8 ng/g) and dominated the OCP composition (84.2% ± 10.2%).…”
Section: Ocpssupporting
confidence: 64%
“…Though the use of these legacy compounds was banned in the early 1980s, HCHs and DDTs were detected at all sediment depths in SGZ and accounted for a large proportion of the OCPs present in the core (30.5 ± 7.5% and 60.9 ± 8.1% of ΣOCP, respectively). The high detection frequency of HCHs and DDTs in the SGZ core is supported by other studies in South China (Guo et al, 2009;Grung et al, 2015). It was assumed that the same trends would be observed for the RLY core as well, however surprisingly, that was not the case, as HCHs and DDTs were rarely detected in the core, and rather chlordanes were detected at higher concentrations (11.2-98.8 ng/g) and dominated the OCP composition (84.2% ± 10.2%).…”
Section: Ocpssupporting
confidence: 64%
“…Because of frequent pest and disease outbreaks, the entire cultivation and management process requires a large amount of pesticide application. If not correctly applied and if the maximum recommended dose rate is not respected, this not only leads to pesticide residues exceeding the standard, but also contaminates the environment . To improve the retention and spreading of the spray liquid on the target surface, the wettability of pear leaves from different ecological environments at different growth stages needs to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…If not correctly applied and if the maximum recommended dose rate is not respected, this not only leads to pesticide residues exceeding the standard, but also contaminates the environment. 37 To improve the retention and spreading of the spray liquid on the target surface, the wettability of pear leaves from different ecological environments at different growth stages needs to be studied. In this study, Yuanping City, Yuci City and Linyi County in Shanxi Province, all with different climates (Table 1), were selected to study surface wettability of pear leaves, and to establish a scientific and rational agrochemical application technique.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown that 1,1-dichloro-2,2-bis(4-chlorophenyl) ethane (4,4′-DDE), the major metabolite of 1,1′-bis(4-chlorophenyl)-2,2,2-trichloroethane (4,4′-DDT), is present at high levels in different environmental media in China (Grung et al 2015; Yin et al 2015; Zhang et al 2013; Zhou et al 2016a) even though technical DDT was prohibited for agricultural use in 1983 (Yu et al 2005). Qiu et al (2005) stated that the use of dicofol in China has become an important source of DDT after the prohibition.…”
Section: Introductionmentioning
confidence: 99%